Conceptualizing online content from a game-theoretic and relational perspective - Lin, Bernice Xiangting (2024)
Online participation involves the creation and consumption of content. However, there has been no explicit agreement on the definition of online content. This obscures the impacts various online content has on online participation. In this article, we propose a conceptual framework to distinguish the wide range of online content, focusing on their relational properties (i.e., cocreation and co-ownership potentials). Consonance between these relational dimensions is expected to influence the overall stability of online participation. Our framework of online content builds on a game-theoretic perspective of online participation: Collective dynamics observed in online participation are modeled by the stag hunt game, and the dilemma that players face is applied to the creation and ownership dimensions of online content. Theoretical implications include informing empirical research in the relationships among content creation, ownership, and online participation; reviewing policymaking related to media ownership structure; and advancing discourse in arts, technology, and media.